2021
DOI: 10.3390/pathogens10030276
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Real-Time PCR Assay for Six Major Carbapenemase Genes

Abstract: The global dissemination of carbapenemase-producing Enterobacteriaceae (CPE) is a major concern in public health. Due to the existence of the diversity of carbapenemases, development of an easily available, cost-effective multiplex detection assay for CPE is required worldwide. Using clinically available and reliable equipment, COBAS® z480 (Roche Diagnostics K.K., Tokyo, Japan), we developed a multiplex real-time PCR assay for the detection of two combinations of carbapenemases; first, blaNDM, blaKPC, and blaI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This technique is used to amplify the targeted DNA sequence by use of hydrolysis probes that are short oligonucleotides, that have a fluorescent reporter dye attached to the 5’end and a quencher dye to the 3’end. The details of primers and probes 22 for blaNDM, blaKPC, blaIMP, blaOXA-48, and blaVIM are shown in Table 1 . We used two multiplex assays to identify two combinations of five carbapenemase genes and an internal control; Set 1 and Set 2 contained blaNDM, blaKPC, blaIMP, blaVIM, and blaOXA-48, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is used to amplify the targeted DNA sequence by use of hydrolysis probes that are short oligonucleotides, that have a fluorescent reporter dye attached to the 5’end and a quencher dye to the 3’end. The details of primers and probes 22 for blaNDM, blaKPC, blaIMP, blaOXA-48, and blaVIM are shown in Table 1 . We used two multiplex assays to identify two combinations of five carbapenemase genes and an internal control; Set 1 and Set 2 contained blaNDM, blaKPC, blaIMP, blaVIM, and blaOXA-48, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In a single-tube reaction, the kit enables the accurate and precise detection of both single and co-present carbapenemase-encoding genes. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…Next, two wells were filled with 10 µL of inoculum, one of which contained imipenem. Gram-negative bacteria that produced metallo β lactamases (MBL) were treated with imipenem as the carbapenemase zinc substrate; positive results were defined as those in which the color of the bacteria changed from red to yellow, orange, or thick orange in comparison to the control well [17][18][19].…”
Section: Carba Np Test For Phenotypical Detection Of Carbapenemase Pr...mentioning
confidence: 99%
“…Cycle threshold values greater than ≤40 were regarded as positive. The kit enables the accurate and precise detection of carbapenemase encoding genes that are present singly or in combination in single tube reactions [19,20].…”
Section: Table 2: Composition Of the Master MIX For Detecting Carbape...mentioning
confidence: 99%
“…Yoshioka et al used two combinations of carbapenemases detection primers, as we did, but selected partially different primers. They concluded that the assay appropriately differentiated the reference or clinical strains harboring each carbapenemase gene without cross reactivity(25). LightMix® Modular carbapenemases Kits detect the main classes of carbapenemases with a high level of accuracy.…”
mentioning
confidence: 99%